2022
DOI: 10.4103/indianjpsychiatry.indianjpsychiatry_409_21
|View full text |Cite
|
Sign up to set email alerts
|

Role of self-compassion and online/offline integration on internet addiction, aggression, and psychological well-being: A mediation analysis

Abstract: Context: Internet addiction is known to harmfully affect psychological health. However, few researches have examined its plausible related factors and respite from its effects. Aim: This study aims to examine the relationship between internet addiction, aggression, psychological well-being, and the mediating effects of self-compassion and online/offline integration, on them. Materials and Methods: Data from 459 university students aged betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Higher self-compassion was negatively associated with increased skills games and time wasters, streaming, digital hoarding, and cyberchondria. Several previous studies showed negative associations between self-compassion and PUI [ 21 , 49 , 50 ]. However, our study is among the first to show associations between self-compassion and specific online behaviour.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Higher self-compassion was negatively associated with increased skills games and time wasters, streaming, digital hoarding, and cyberchondria. Several previous studies showed negative associations between self-compassion and PUI [ 21 , 49 , 50 ]. However, our study is among the first to show associations between self-compassion and specific online behaviour.…”
Section: Discussionmentioning
confidence: 94%
“…The median of the scale completion time was 19 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) min. In sum, 2913 participants entered the study; however, 23 % (n = 690) either did not finish the study or provided blank sections in the survey; thus, their data were removed from the sample, leaving a final sample of 2223 individuals in total, from Italy (n = 621; 27.9%); Spain (n = 257; 11.6%); United Kingdom (n = 126; 5.7%); Lithuania (n = 221; 9.9%); Portugal (n = 172; 7.7%); Japan (n = 68; 3.1%); Hungary (n = 47; 2.1 %); and Brazil (n = 711; 32.0%).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation